Does market access mitigate the impact of seasonality on child growth? Panel data evidence from northern Ethiopia - Abay, Kibrewossen; Hirvonen, Kalle (International Food Policy Research Institute, 2016)
Seasonality in agricultural production continues to shape intra-annual food availability and prices in low-income countries. Using high-frequency panel data from northern Ethiopia, this study attempts to quantify seasonal fluctuations in children's weights. In line with earlier studies, we document considerable seasonality in children’s age and height adjusted weights. While children located closer to local food markets are better nourished compared to their counterparts residing in more remote areas, their weights are also subject to considerable seasonality. Further analysis provides evidence that children located closer to food markets consume more diverse diets than those located farther away. However, the content of these diets varies across seasons: children are less likely to consume animal source foods during the lean season.